2017
DOI: 10.1016/j.anorl.2017.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Undifferentiated carcinoma of nasopharyngeal type in children: Clinical features and outcome

Abstract: Undifferentiated carcinoma of nasopharyngeal type in children represents 6% of all cases of UCNT managed in our institutions. It is often discovered at an advanced stage. Sequential treatment combining chemotherapy and radiotherapy achieves an excellent local control rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…A higher T stage has been reported as an unfavorable factor for survival (27,34). In the present study, higher plasma EBV DNA and T4 category were independent predictors for DMFS and DFS.…”
Section: Discussionsupporting
confidence: 59%
“…A higher T stage has been reported as an unfavorable factor for survival (27,34). In the present study, higher plasma EBV DNA and T4 category were independent predictors for DMFS and DFS.…”
Section: Discussionsupporting
confidence: 59%
“…Zrafi WS et coll. [17] quant à eux retrouvaient 90% de masses cervicales, c'est le cas aussi de Ndiaye IC et coll. [18] avec des adénopathies dans 73.33% des cas.…”
Section: Discussionunclassified
“…Neck mass was the most prevalent impetus to seek treatment, as shown in previous studies. 7,9,19 A study in China reported that neck mass affected up to 40.9% of pediatric patients and cranial nerve involvement in 3% patients. 7 This percentage was lower than in our study (Table 2), but neck mass was the most common symptom.…”
Section: Discussionmentioning
confidence: 99%
“…6 Common symptoms in pediatric patients are neck masses, blocked nose, and hearing problems. [7][8][9] These symptoms are sometimes regarded as other diseases and, therefore, misdiagnosed. Owing to their locoregional mass extension, some patients present with cranial nerve palsies causing diplopia, trismus, as well as facial numbness and pain.…”
mentioning
confidence: 99%